Power Control for a Wind Power Generation from SCIG and Harmonic Current Filtering - Santos, Ângelo Marcílio Marques dos (2020)
The main contribution of this paper is to present a proposal for the development of an active power filter (APF) for a wind power generation system connected to the electric grid, using the three-phase induction generator with squirrel cage rotor (SCIG). In the induction generator side converter (IGSC) the power control is done by the magnetizing current and electromagnetic torque in coordinates dq. Thus, the wind system controls the active and reactive powers, as well as performing the active filtering function in the grid currents. Harmonic compensation is performed by an algorithm applied to the grid side converter (GSC). That technique improves the power quality and keeps the voltage at DC bus. The studied system was mathematically modeled and simulated using the Matlab / Simulink software. When SCIG provides 2 kW of active power, the THD from 18,94% (without APF) was reduced to 3,93% for GSC operating with APF function.